Problems Faced by Domestic Child Workers in Katmandu Metropolitan City, Nepal, 2006 - Kaphle, Maheshor (Journal of Manmohan Memorial Institute of Health Sciences, 2014)
Children working in an employer?s house with or without wages are known as domestic child workers. Domestic child workers (DCWs) are basically employed to perform domestic chores such as washing dishes, cooking, cleaning the house. Objectives: to identify the problems faced by domestic child workers. Study design and sample size: a cross-sectional study was conducted with 200 domestic child workers. Study variables: age sex reason of work, type of work, hours of work per day, monthly wages and health problems. Statistical analysis: chi-square test, z-test, ANOVA etc. result and conclusion: the study found that near about two-third of DCWs was girl. Mean age was 12.32years (SD 0.13). Main cause of migration to city from home town was to study followed by earning money. Most of them do all household work for 12 to 18 hours per day. So they did not get adequate time for rest/sleep. Majority of them did not get weekly leave. More than forty percent of DCWs were working without wages. Most of them who get wages, earn below 500 rupees (6.66) per month. Most of them had not formal contract and more than two-third of them not was willing to leave current work due to study purpose and not getting formal schooling as current problems. DCWs who work more hours per day get more health problems. Most of them suffered from fever headache and cold/cough. More than two third of DCWs were abused during domestic work. Most of them were scolded by their employers. To go further and want to do vocational training were their future aspiration. DOI: http://dx.doi.org/10.3126/jmmihs.v1i1.9899 Journal of Manmohan Memorial Institute of Health Sciences Vol.1(1) 2011; 36-39